Polyolefin Compounds and Materials Fundamentals and Industrial Applications - Al-Ali AlMa'adeed, Mariam; Krupa, Igor.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book describes industrial applications of polyolefins from the researchers' perspective. Polyolefins constitute today arguably the most important class of polymers and polymeric materials for widespread industrial applications. This book summarizes the present state of the art. Starting from fundamental aspects, such as the polymerization techniques to synthesize polyolefins, the book introduces the topic. Basic knowledge about polyolefin composites and blends is explained, before applications aspects in different industry sectors are discussed. The spectrum comprises a wide range of applications and industry sectors, such as the packaging and food industry, the textile industry, automotive and buildings, and even biomedical applications. Topics, which are addressed in the various chapters, comprise synthesis and processing of the materials; their classification; mechanical, physical and technical requirements and properties; their characterization; and many more. In the end of the book, even the disposal, degradation and recycling of polyolefins are addressed, and light is shed on their commercial significance and economic value. In this way, the book follows the entire 'lifetime' of polyolefin compounds and materials: from their synthesis and processing, over applications, to the recycling and reuse of disposed or degraded polyolefin substrates.
Keywords: Polymers; Ceramic materials; Chemistry, Technical; Industrial engineering; Production engineering; Polymers; Ceramics; Industrial Chemistry; Industrial and Production Engineering